2010
DOI: 10.1080/07399332.2010.486881
|View full text |Cite
|
Sign up to set email alerts
|

Religiosity and Sexuality: Experiences of Brazilian Catholic Women

Abstract: The purpose of this study was to describe the experiences of a group of Catholic women related to the orientations received from priests and parents and their influence on sexual attitudes. The oral history method was used to interview 17 Catholic women. Three categories summarize women's experiences: orientations about sexuality received from priests; lack of orientation or existence of open dialogue about sexuality: distinct experiences in the family context; adherence or repudiation; and distinct attitudes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 23 publications
1
1
0
6
Order By: Relevance
“…Some studies have shown that practicing a religion reduces risk behaviors for STI by establishing behavioral norms for its followers (43)(44)(45) . In the present study, individuals who reported some religion presented lower positivity to STI, and this variable was negatively associated with these infections, reinforcing this hypothesis (46)(47) . to disease prevention and treatment (48)(49) .…”
Section: CIsupporting
confidence: 86%
“…Some studies have shown that practicing a religion reduces risk behaviors for STI by establishing behavioral norms for its followers (43)(44)(45) . In the present study, individuals who reported some religion presented lower positivity to STI, and this variable was negatively associated with these infections, reinforcing this hypothesis (46)(47) . to disease prevention and treatment (48)(49) .…”
Section: CIsupporting
confidence: 86%
“…A previous study focused on Catholics (Hoga, Tibúrcio, Borges, & Reberte, 2010) described the advice regarding sexuality and contraceptive behaviors that women received from priests and parents. Catholic women also received advice to preserve virginity until marriage, to be a good girl and marry, and to have children only after marriage.…”
Section: Discussionmentioning
confidence: 99%
“…Assim, é importante que os profissionais da saúde, ao atenderem mulheres religiosas, verifiquem se suas escolhas são conscientes, provendo um espaço para elas refletirem sobre essa temática nos serviços de saúde (Hoga et al, 2010).…”
Section: Religiãounclassified
“…Em aspectos referentes à sexualidade, a figura paterna foi retratada como "fechada e brava", tendo a mãe a função de "porta-voz" das diretrizes do pai. O único pai que abor-dou essa questão foi o de P4, já que conversas sobre esse tema geralmente são realizadas entre mães e filhas (Hoga et al, 2010). No entanto, raramente ocorreram diálogos, e toda referência ao assunto foi tratada com conotação negativa e punitiva pelas famílias, não tendo caráter esclarecedor ou informativo.…”
Section: Famíliaunclassified